2018
DOI: 10.1055/s-0038-1676647
|View full text |Cite
|
Sign up to set email alerts
|

Rigid Bronchoscopy

Abstract: Rigid bronchoscopy is one of the oldest medical techniques used in the respiratory and thoracic fields. Even though its use declined after the development of flexible bronchoscopy, it has again gained importance with the growth of interventional pulmonology, becoming a critical technique taught as part of the training in this subspecialty. The therapeutic advantages compared to other approaches of thoracic pathologies makes rigid bronchoscopy a primary component in the present and future of interventional pulm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Although there are no prospective studies reporting the incidence of ITI due to endotracheal tube intubation, the reported incidence is 0.05–0.37% [ 2 ]. Although rigid bronchoscopy may result in tracheal injury, the incidence is unknown [ 11 , 12 ]. In this case, ITI occurred during rigid bronchoscopy and was relieved by stent placement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there are no prospective studies reporting the incidence of ITI due to endotracheal tube intubation, the reported incidence is 0.05–0.37% [ 2 ]. Although rigid bronchoscopy may result in tracheal injury, the incidence is unknown [ 11 , 12 ]. In this case, ITI occurred during rigid bronchoscopy and was relieved by stent placement.…”
Section: Discussionmentioning
confidence: 99%
“…Although some cases have required urgent thoracotomy, cases have also been reported in which spontaneous healing of the tracheal injury has occurred with conservative management [ 3–10 ]. Although rigid bronchoscopy has been used and is preferred in the field of interventional bronchoscopy, rigid bronchoscopy is a potentially hazardous technique [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, one disadvantage is the high recurrence rate [ 10 ]. Recently, bronchoscopic interventions have been widely applied in the management of massive hemoptysis, demonstrating a high success rate [ 11 , 12 ]. The primary goal of bronchoscopic intervention treatment is to clear blood and secretions, maintain an unobstructed airway, prevent asphyxia, and achieve local hemostasis [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%